Rechtsgeschichte und Ordnungsdenken. Zum rechtshistorischen Werk von Paolo Grossi - Thomas Duve (Rechtsgeschichte - Legal History)
Paolo Grossi (1933–2022) was one of the most inﬂuential legal historians of his generation. His works on the legal history of the Middle Ages and the modern period, not least his critique of the law of the modern age, have been widely received in Europe and Latin America. The article, which is also a tribute to the long-standing member of the Advisory Board of the Max Planck Institute for European Legal History, reconstructs some aspects of his legal historical work, analyses the close connection between legal history and legal theory in his thought, and asks about the potential of Grossi’s method for legal history today.